Identification of E.coli. In Sudanese White Soft Cheese (University of Khartoum Engineering Journal, 2022)
Study of dairy products is of great interest to the daily consumer . This research studied the total count of bacteria and the identification of the Escherichia coli (E.coli) bacteria of ready for sale and consumption white cheese.Three samples of locally produced cheese were collected from market in Khartoum at different dates and stored in polypropylene (PP) packaging at temperature of 4oC. The different samples were then subjected to laboratory tests to determine the total bacterial colonies and hence the total count of bacteria and E.coli in white cheese.The quality of white cheese including chemical and microbial characteristics which are affected by several factors were studied. The average bacterial colonies for cheese showed differences at two different dilutions (10-4and 10-5) of the Agar medium used. The average numbers of the bacterial colonies for the three samples were 15.54, 11.74 and 9.79. The biochemical reaction of the isolated bacteria from the three samples of white cheese showed no E.coli presence, gram negative bacteria, however, was found to be present.